Optimasi Ekstraksi DNA Genomik Probiotik Lactobacillus plantarum IIA-1A5 dari Daging Sapi Peranakan Ongole untuk Sekuensing Genom Utuh - Budiman, C.; Arief, I. I.; Yusuf, M. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2018)
Lactobacillus plantarum IIA-1A5 is an Indonesian probiotic bacterium isolated from Ongole grade cattle. This strain has demonstrated series of benefical properties and promising to be further applied in development of functional foods. Attempts to further exploit this strain require comprehensive understanding on its molecular properties, in particular is the genes responsible for its probiotic properties.Whole genome sequencing (WGS) is currently an affordable tool to fully decipher genetic organization of the bacteria, yet often limited by the requirement of high amount of high quality of genomic DNA ofsample. This study aims to develop an optimum method for obtaining high quality genomic DNA of L. plantarum IIA-1A5 in sufficient amount of WGS study. To address, genomic DNA of L. plantarum IIA-1A5 was extracted from growth phase of adaptation, exponential and stationary. The result showed that exponential and stationary phases were able to yield genomic DNA higher than minimum requirement for WGS. Nevertheless, the quality of genomic DNA from both phases were considerably low, according to their 260/280 and 260/230 ratio. The worst quality was found on 260/280 ratio referring to thepresence of high amount of proteinaceous compounds in the sample. Further optimization was done on genomic DNA from stationary phase by adding proteinase K at various incubation time. It showed that the incubation for 7.5 to 10 hours yielded acceptable purity and amount of genomic DNA for WGS. In addition, we also observed a trade-off phenomenon of yield-purity genomic DNA of L. plantarum IIA-1A5. Altogether, the optimized method here should contribute to further molecular studies of this probiotic strain.